2021
DOI: 10.1111/cas.15017
|View full text |Cite
|
Sign up to set email alerts
|

Delta‐like canonical Notch ligand 3 as a potential therapeutic target in malignancies: A brief overview

Abstract: Delta‐like canonical Notch ligand 3 (DLL3) is a member of the Delta/Serrate/Lag2 (DSL) Notch receptor ligand family and plays a crucial role in Notch signaling, which influences various cellular processes including differentiation, proliferation, survival, and apoptosis. DLL3 is expressed throughout the presomitic mesoderm and is localized to the rostral somatic compartments; mutations in DLL3 induce skeletal abnormalities such as spondylocostal dysostosis. Recently, DLL3 has attracted interest as a novel mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…4 E). The Notch signaling pathway is involved in various inflammatory diseases and cancers [ 16 , 17 ]. The KEGG pathway enrichment analysis showed that it was one of the most altered pathways.…”
Section: Resultsmentioning
confidence: 99%
“…4 E). The Notch signaling pathway is involved in various inflammatory diseases and cancers [ 16 , 17 ]. The KEGG pathway enrichment analysis showed that it was one of the most altered pathways.…”
Section: Resultsmentioning
confidence: 99%
“…As a critical transcription factor involved in epithelial-mesenchymal transition, TWIST1 overexpression can enhance the susceptibility to chemotherapy drugs by promoting cell cycle entry and, thus, improve AML patients' outcomes (Chen et al, 2015;Wang et al, 2015). DLL3 was an atypical Notch ligand that has been investigated in many tumors as a therapeutic target (Matsuo et al, 2021). In AML, improved survival was observed in high expression of DLL3, and it may function by cell proliferation regulation (Yan et al, 2010;Takam Kamga et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that NOTCH 1 expression was absent in SPC ( 14 ), which corresponded to the fact that INSM1 is essential for neuroendocrine differentiation, and Notch 1 negatively regulates neuroendocrine differentiation ( 6 , 14 ). Moreover, DLL3 plays an important role and is considered an autonomous inhibitor of Notch signalling, and SPCs show positive immunoreactivity for Notch 2 and Notch 3 ( 14 , 20 ). DLL3 expression was not detected in all patients with SPC in the present cohort, consistent with the results of a previous study ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, the frequency of loss of ATRX and DAXX expression and its prognostic significance in SPC patients has not yet been analysed. Moreover, δ-like canonical Notch ligand 3 (DLL3), which plays an important role in Notch signalling, is frequently expressed in neuroendocrine-related tumours, such as neuroendocrine carcinomas of the lungs ( 20 ). However, DLL-3 expression and its prognostic significance in SPC have not yet been analysed.…”
Section: Introductionmentioning
confidence: 99%